Protein corona changes mediated by surface modification of amorphous silica nanoparticles suppress acute toxicity and activation of intrinsic coagulation cascade in mice. (19th June 2015) - Yoshida, Tokuyuki; Yoshioka, Yasuo; Morishita, Yuki; Aoyama, Michihiko; Tochigi, Saeko; Hirai, Toshiro; Tanaka, Kota; Nagano, Kazuya; Kamada, Haruhiko; Tsunoda, Shin-ichi; Nabeshi, Hiromi; Yoshikawa, Tomoaki; et al.
Abstract Recently, nanomaterial-mediated biological effects have been shown to be governed by the interaction of nanomaterials with some kinds of proteins in biological fluids, and the physical characteristics of the nanomaterials determine the extent and type of their interactions with proteins. Here, we examined the relationships between the surface properties of amorphous silica nanoparticles with diameters of 70 nm (nSP70), their interactions with some proteins in biological fluids, and their toxicity in mice after intravenous administration. The surface modification of nSP70 with amino groups (nSP70-N) prevented acute lethality and abnormal activation of the coagulation cascade found in the nSP70-treated group of mice. Since our previous study showed that coagulation factor XII played a role in the nSP70-mediated abnormal activation of the coagulation cascade, we examined the interaction of nSP70 and nSP70-N with coagulation factor XII. Coagulation factor XII bonded to the surface of nSP70 to a greater extent than that observed for nSP70-N, and consequently more activation of coagulation factor XII was observed for nSP70 than for nSP70-N. Collectively, our results suggest that controlling the interaction of nSP70 with blood coagulation factor XII by modifying the surface properties would help to inhibit the nSP70-mediated abnormal activation of the blood coagulation cascade.